In This Issue - Michael Scriven (The Evaluation Center at Western Michigan University, 2006)
This is a particularly exciting issue, for several reasons. First, we have an important paper by Tom Cook (describing what is special about the role of experiments, etc.) which goes a long way towards defining a compromise on the 'causal wars' issues, as I try to spell out in a few comments, and Jane Davidson discusses in her editorial. We hope Professor Cook will reply to both comments in the next issue if he disagrees with them. And we hope readers will consider adding their input to this important discussion.